2019
DOI: 10.1111/fcsr.12305
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Cooking Education among High School Students

Abstract: Cooking is a basic life skill and promotes a more healthful diet. However, many young adults lack cooking confidence. Eleven focus groups with 71 total participants were conducted to understand perceptions of cooking education among high school students. Students who had taken cooking classes displayed cooking confidence, developed additional non‐cooking‐related skills, and valued the courses. Students believed cooking is a life skill, would like to learn more skills and about cultural cuisines, and thought co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…With respect to didactics, My Cookery aims to integrate experiential learning, student co-determination and the active use of taste competences during cooking (Leer & Wistoft, 2018). Recent research has shown that this combination of approaches shows good potential in enhancing student learning outcomes in food education (Christensen and Wistoft, 2016; Hansen et al, 2019 Häikiö et al, 2020; Mäkelä et al, 2018; Ozorak, 2013). However, the implementation of these didactics alongside the provision of children’s cookbook offers a unique way of applying these approaches, and therefore, research on the use of the method is also sparse.…”
Section: My Cookerymentioning
confidence: 99%
“…With respect to didactics, My Cookery aims to integrate experiential learning, student co-determination and the active use of taste competences during cooking (Leer & Wistoft, 2018). Recent research has shown that this combination of approaches shows good potential in enhancing student learning outcomes in food education (Christensen and Wistoft, 2016; Hansen et al, 2019 Häikiö et al, 2020; Mäkelä et al, 2018; Ozorak, 2013). However, the implementation of these didactics alongside the provision of children’s cookbook offers a unique way of applying these approaches, and therefore, research on the use of the method is also sparse.…”
Section: My Cookerymentioning
confidence: 99%
“…Classroom‐based cooking education has been in existence since the early 1900s as part of home economics courses (Weigley, ). Hansen, Drake, and Vollmer () found high school cooking classes fostered cooking confidence, a sense of community and accomplishment, and development of professional skills such as problem‐solving, teamwork, time management, and improved social skills. Also, Watson et al.…”
Section: Review Of Literaturementioning
confidence: 99%